Test Anxiety and its Impact on first year University Students and the over View of mind and body Intervention to Enhance coping Skills in Facing Exams - Farrahdilla, Hamzah; Vidya, Bhagat; Khairi, Che Mat (2018)
Test anxiety has an impact on students either negative or positive. It is normal to have exam anxiety that help the students to prepare them for facing examination on the other hand it can also distress the students ‘and disturb them physically, emotionally; cognitively that can result in poor examination performance. The current study had analysed the past reviews regarding test anxiety impacting student performance in their examinations. The purpose of this study is to give overview of mind-body interventions for first year university students who facing test anxiety. This literature review was completed using electronic databases. The current study had analysed reviewing 70 articles from year 1961 to 2017. The reviewed articles were regarding test anxiety it’s negative and positive correlates, Mind- body intervention and its benefits. Current study concludes though the test anxiety is common among students the academicians and educationalists in the universities should have awareness about negative and positive aspects of this test anxiety that can impact students’ performance. Further, current study suggests that practicing mind- body interventional programmes in the university to promote overall health and wellbeing among student population.